Disruption of Functional Brain Networks Underlies the Handwriting Deficit in Children With Developmental Dyslexia - Liu, Zhengyan; Li, Junjun; Bi, Hong-Yan; Xu, Min; Yang, Yang (Frontiers in Neuroscience, 2022)
Developmental dyslexia (DD) is a neurological-based learning disorder that affects 5-17.5% of children. Handwriting difficulty is a prevailing symptom of dyslexia, but its neural mechanisms remain elusive. Using functional magnetic resonance imaging (fMRI), this study examined functional brain networks associated with handwriting in a copying task in Chinese children with DD (n =17) and age-matched children (n = 36). We found that dyslexics showed reduced network connectivity between the sensory-motor network (SMN) and the visual network (VN), and between the default mode network (DMN) and the ventral attention network (VAN) during handwriting, but not during drawing geometric figures. Moreover, the connectivity strength of the networks showing group differences was correlated with handwriting speed, reading and working memory, suggesting that the handwriting deficit in DD is linked with disruption of a large-scale brain network supporting motoric, linguistic and executive control processes. Taken together, this study demonstrates the alternations of functional brain networks associated with the handwriting deficit in Chinese dyslexia, providing a new clue for the neural basis of DD.